Empowering Intelligent Systems: Vision and Image Processing in the Age of AI, IoT, and Data Analytics - Hawari Bin Ghazali, Kamarul (UNIMUS Web Conferences, 2025)
Technology combines AI, computer vision, and sensor fusion to track items customers pick up and automatically charge them when they leave. Vision systems and sensors detect when products are taken or returned to shelves, while machine learning models analyze this data to optimize inventory management and inform customer behavior. The Power of Vision and Image Processing: 1) How vision systems interpret and analyze visual data in real-time, 2) Advances in Deep Learning (DL) and Machine Learning (ML) in image processing, 3) Benefits: Autonomous decision-making, improved efficiency, and higher accuracy.